PENERAPAN NUMBERED HEAD TOGETHER (NHT) DALAM PENINGKATAN KEMAMPUAN KOGNITIF PESERTA DIDIK SEKOLAH MENENGAH PERTAMA - Zuni Mitasari; Maria Rambu Tupa Dairu; Hasminar Rachman Fidiastuti (Inteligensi : Jurnal Ilmu Pendidikan, 2022)
This research was conducted to apply the NHT (Numbered Head Together) model in improving the cognitive abilities of junior high school students, using a quasi-experimental, where the sample used was 33 students in each control class and the experiment through random sampling. The instrument used is a multiple choice test to determine the level of cognitive abilities of students. The results obtained in the experimental class using NHT showed that there was an increase in the results from 69 to 80 during the pre-test and posttest, and continued with statistical tests which resulted in a significance value of 0.034 0.05 which indicated that there were differences in the cognitive abilities of students with the application of NHT. This is because the advantages of the NHT model are able to create a sense of responsibility in students towards assignments, student learning becomes more focused, able to bring up the question and answering process and can increase the activity and interest of students and conclude that the application of the NHT model can improve students' cognitive abilities on the motion system material in living things in class VIII at SMP Negeri 3 Waibakul has increased.